Sleep apnea is associated with reduced in-hospital mortality in patients admitted for acute heart disease - Maurice Moser; Florent Baty; Gian-Reto Kleger; Micha T. Maeder; Hans Rickli; Otto D. Schoch; Martin H. Brutsche (PLoS ONE, 2025)
Background: Sleep apnea (SA) is an independent risk factor for many cardiovascular diseases. The impact of SA on the outcome of patients hospitalized due to cardiovascular diseases is controversial. Recent studies indicated fewer fatal cardiac events associated with SA in a setting where co-factors may play an important role. The aim of the current study was to investigate in-hospital mortality of patients hospitalized with acute heart diseases with or without SA. Methods and findings: In this retrospective, nested case-control study, data were extracted from a Swiss-wide hospitalization database. All patients with a primary diagnosis of acute heart disease were identified. Among those patients, all patients with a co-diagnosis of SA were extracted together with a control population matching the cases 1:1 for age, gender, month of hospitalization and Charlson’s comorbidity index. The impact of SA and other comorbidities was investigated using competing risks survival analysis. Between 2010 and 2020, 744,455 hospitalizations occurred with a primary diagnosis of acute heart disease in Switzerland among which 21,904 had a SA co-diagnosis. Patients with SA had a longer length of stay, were more often rehospitalized and had a higher number of comorbidities. On the other hand, they had a lower in-hospital mortality compared to controls (1.9 [1.8 to 2.1]% vs. 3.9 [3.7 to 4.2]%; subdistribution hazard ratio: 0.40 [95% confidence interval: 0.35 to 0.45], p < 0.001). Several comorbidities significantly interacted with SA. Obesity and hypertension were associated with a lower in-hospital mortality in both SA and non-SA. Shock was more frequent and significantly more harmful in non-SA patients. Conclusions: A SA co-diagnosis in patients hospitalized due to acute heart disease was associated with a lower in-hospital mortality. Explanations for this survival paradox include the interplay of interacting comorbidities and hypoxic preconditioning contributing to the protective effect of SA.